A model of tourists' loyalty: the case of Airbnb. (12th March 2018) - Lalicic, Lidija; Weismayer, Christian
Abstract : Purpose: Airbnb, a popular peer-to-peer accommodation platform, exceeds the yearly revenue of hotel chains, such as Marriot and Hilton. However, the reason why consumers engage with peer-to-peer accommodations and become loyal is not completely clear yet. This study aims to investigate Airbnb as a service setting. In doing so, more insights into the relevance of concepts, such as service quality (SQ) and hospitality factors, to explain consumers' behavioral intentions with peer-to-peer accommodations and its effect on loyalty can be gained. Design/methodology/approach: Through an online survey among Airbnb users and structural equation modeling, the model connecting the measurement constructs is analyzed. Findings: This study shows that SQ and importance of having social and authentic experiences are significant antecedents of tourists' loyalty toward Airbnb hosting services. Interestingly, perceived economic benefits do not impact the level of loyalty, neither does feelings of perceived reduce risk. Originality/value: The theoretical contributions reveal tourists' behavioral patterns in the peer-to-peer accommodation context influenced by standard service factors used for other types of accommodations. This study has particular implications for the accommodation sector when segmenting customers according to their needs and designing appropriate marketing strategies. Abstract : 论游客忠诚模型：Airbnb案例分析 摘要 研究目的: Airbnb是目前流行的大众提供住宿民宿的在线平台，其年收益已经超过很多连锁酒店，包括万豪和希尔顿在内。然而， 关于消费者如何消费和热衷于这种Airbnb民宿的原因还知之尚浅。本研究主要以Airbnb为题进行研究，其研究结果深刻讨论Airbnb相关概念，比如服务质量和酒店管理因素等， 以解释分析消费者行为动机和游客忠诚的联系纽带。 研究设计: 本研究采用在线问卷采样的形式，Airbnb客人在线填写问卷，其样本经过结构方程模型（SEM）技术，以分析相关模型结构。 研究结果: 本研究结果表明服务质量、社交体验、以及正宗的当地游客体验对于游客Airbnb忠诚度有着显著促进作用。饶有趣味的地方是，游客对于省钱和感知风险等方面并未对其Airbnb忠诚度有任何显著影响。 研究价值: 在理论意义方面，本研究深刻探讨游客对于大众提供住宿服务的行为模式。在实践意义方面，本研究结果对细分客户市场的需求探索和营销策略制定方面有着特别贡献。